2019
DOI: 10.1093/ntr/ntz077
|View full text |Cite
|
Sign up to set email alerts
|

Brain Marker Links Stress and Nicotine Abstinence

Abstract: Background Subjective stress is a well-documented predictor of early smoking relapse, yet our understanding of stress and tobacco use is limited by reliance on self-reported measures of stress. We utilized a validated functional neuroimaging paradigm to examine whether stress exposure during early abstinence alters objective measures of brain function. Methods Seventy-five participants underwent blood oxygen level dependent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
0
8
0
3
Order By: Relevance
“…The number of participants was relatively low; thus, we have performed the p-value correction via random permutations when identifying ROIs and p-value correction as well as bootstrapping when analyzing the association between the RT and neuronal activations. Despite our effort to alleviate the weakness of a relatively small sample size, future research recruiting more participants is warranted to evaluate the brain regions associated with the stress response with potentially greater statistical significance than our results (Allenby et al, 2020). In addition, the distribution of our relatively small samples may deviate from population normal distribution; accordingly, we applied random permutation and non-parametric bootstrapping with replacement to resolve the potential bias of statistical inference (Briggs et al, 1997;Barber and Thompson, 2000;Simar and Wilson, 2000;Saha et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…The number of participants was relatively low; thus, we have performed the p-value correction via random permutations when identifying ROIs and p-value correction as well as bootstrapping when analyzing the association between the RT and neuronal activations. Despite our effort to alleviate the weakness of a relatively small sample size, future research recruiting more participants is warranted to evaluate the brain regions associated with the stress response with potentially greater statistical significance than our results (Allenby et al, 2020). In addition, the distribution of our relatively small samples may deviate from population normal distribution; accordingly, we applied random permutation and non-parametric bootstrapping with replacement to resolve the potential bias of statistical inference (Briggs et al, 1997;Barber and Thompson, 2000;Simar and Wilson, 2000;Saha et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Analiza dostępnych prac wskazuje, że MIST jest najczęściej stosowany do oceny czynnościowej aktywności mózgu [20][21][22][23][24]. Wykorzystuje się także pomiar reakcji skórno-galwanicznej [20,22] i miary subiektywne [21].…”
Section: Montreal Imaging Stress Task (Mist)unclassified
“…The Montreal Imaging Stress Task is a psychosocial stress task that requires solving difficult mental arithmetic problems while receiving negative performance feedback. Researchers have found that taking the Montreal Imaging Stress Task while undergoing fMRI not only increased subjective measures of stress [55] but also induced significantly greater activation in the inferior frontal gyrus, ACC, precuneus, and supramarginal gyrus in deprived smokers (24 hours of abstinence compared with the satiety state) [56] and non-deprived smokers [55] (Table 1). Further correlation results revealed that an abstinence-induced change in the brain response to stress is positively associated with a change in self-reported stress [56].…”
Section: Potential Neural Mechanisms Of Withdrawal Symptomsmentioning
confidence: 99%
“…Researchers have found that taking the Montreal Imaging Stress Task while undergoing fMRI not only increased subjective measures of stress [55] but also induced significantly greater activation in the inferior frontal gyrus, ACC, precuneus, and supramarginal gyrus in deprived smokers (24 hours of abstinence compared with the satiety state) [56] and non-deprived smokers [55] (Table 1). Further correlation results revealed that an abstinence-induced change in the brain response to stress is positively associated with a change in self-reported stress [56]. Therefore, investigating stress-related activation during nicotine withdrawal may identify those who are most vulnerable to relapse and represent a target for novel pharmacological intervention.…”
Section: Potential Neural Mechanisms Of Withdrawal Symptomsmentioning
confidence: 99%